(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines psychological factors influencing the effectiveness of preparation and competitive performance of basketball players. Contemporary scientific approaches to the development of cognitive, emotional-volitional, and motivational components of psychological training in team sports are analyzed. A model of psychological preparation for basketball players is presented, which includes four main components: cognitive preparation, emotional-volitional stability, motivational support, and team interaction. The importance of integrating psychological methods into the training process, considering the specific roles of players, is substantiated. The role of forming professional competence in future coaches-teachers is emphasized as a key factor in improving the quality of the training process. Recommendations for coaches on the practical application of psychological techniques in basketball are provided. Research in the field of sports psychology indicates that the level of development of cognitive processes, volitional qualities, and the motivational sphere directly affects game performance. Psychological preparation should be an integral part of the training process alongside physical and technical training. The preparation of coaches-teachers in accordance with modern models of professional competence is a key factor in improving the quality of the training process. Thus, the analysis of contemporary scientific works indicates that the combination of physical and psychological training methods is an important prerequisite for the harmonious development of the individual, the enhancement of competitive performance, and the formation of stable psycho-emotional characteristics. Psychological preparation of basketball players is an integral component of the training process, as it ensures the development of stable cognitive, emotional-volitional, and motivational qualities necessary for achieving high sports results. In basketball, as a dynamic team sport, significant roles are played by the speed of decision-making, the ability to concentrate attention, emotional stability, and the capacity to interact effectively with teammates. Analyzing the works of researchers, it has been identified that key cognitive processes in basketball include attention (concentration, distribution, switching); thinking (tactical, analytical, predictive); and memory (memorization of combinations, signals, game patterns). Emotional-volitional preparation of basketball players ensures the athlete’s ability to perform effectively under stressful conditions, maintaining self-control and confidence in their actions. The motivational component of an athlete is a key factor in sustaining long-term sports activity and progress. Game effectiveness depends not only on individual abilities but also on the quality of team interaction.